The Kuznets Curve and the Impact of Various Income Sources on the Link Between Inequality and Development - Joseph Deutsch; Jacques Silber (Bar-Ilan University, Department of Economics, 2001)
To understand the process described by the Kuznets curve a decomposition of the Gini Index by income sources is used that emphasizes the role of three components measuring the impact of the shares of the sources, the degree to which they are unequally distributed and their correlation with total income. The rising section of the Kuznets curve is mainly the consequence of the increasing share of wages while the declining section is related to the declining share of entrepreneurial income and the negative correlation between transfers and total income. The data sources were provided by the International Labour Office.
Keywords: I3; O1; 330